2001
DOI: 10.1103/physrevb.64.184404
|View full text |Cite
|
Sign up to set email alerts
|

Strain effect and the phase diagram ofLa1xBaxMnO

Abstract: We report magnetic and transport properties of La 1Ϫx Ba x MnO 3 (xϭ0.05-0.33) epitaxial thin films. Compared with the corresponding bulk materials, the ferromagnetic transition temperature is reduced in the compressive strained La 1Ϫx Ba x MnO 3 thin films with xϭ0.3 and 0.33, but enhanced significantly in the tensile strained thin films with xр0.2. Especially, ferromagnetism and low field colossal magnetoresistance effect were observed around room temperature in xϭ0.1 thin film, and as xϭ0.05, a spin-canting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(148 citation statements)
references
References 25 publications
4
139
1
4
Order By: Relevance
“…Strain effects further modify the transport properties of manganite thin films by promoting long-range charge ordering. [27][28][29] We found that the resistance of films with thicknesses from 30 to 75 nm falls in the measurement range of our experimental setup. The transport properties of PCSMO films with various thicknesses are shown in Fig.…”
mentioning
confidence: 75%
“…Strain effects further modify the transport properties of manganite thin films by promoting long-range charge ordering. [27][28][29] We found that the resistance of films with thicknesses from 30 to 75 nm falls in the measurement range of our experimental setup. The transport properties of PCSMO films with various thicknesses are shown in Fig.…”
mentioning
confidence: 75%
“…The extent of in-plane strain is clearly seen to affect magnetic properties of the manganese perovskites La 1Ϫx A x MnO 3 . [9][10][11][12][13][14][15][16][17] These are also local moment ferromagnetic systems. Unfortunately, the band structure must take into account a realistic model of the surface band structure and surface composition in such systems, which can be quite complex in alloys and perovskites, 64 -68 so that a comparison, similar to the one presented here, between the experimental band structures in the perovskite systems with theory presents a very significant challenge.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Compression of gadolinium is seen to lead to a suppression of T c , 3,6 while expansion leads to an increase of T c . 7,8 Not only does strain affect the magnetic properties, as now detailed fairly extensively for the perovskites, [9][10][11][12][13][14][15][16][17] but it has long been established that the lattice constant has a profound influence on the electronic structure, 18 -20 even for the thinnest of thin films. [21][22][23][24][25][26] Gd͑0001͒ grown on Mo͑112͒ exhibits a substantial inplane expansive strain compared to a similar thickness of Gd͑0001͒ on W͑110͒.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for LSMO, tensile strain was shown to reduce the Curie ordering temperature, T C , and this was successfully explained in terms of double exchange: the increase of the in-plane Mn-O bond length leads to a reduction of the hopping term between Mn 3+ -Mn 4+ , therefore reducing T C (see below) [5]. However, for other manganites, such as La 1−x Ba x MnO 3 , a tensile strain was found to enhance T C [9]. Therefore, a thorough understanding has not yet been achieved, due to contradictory results.…”
Section: Introductionmentioning
confidence: 99%